FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MENGKONVERSI LAHAN PERTANIAN MENJADI LAHAN NON PERTANIAN (Studi Kasus : Petani Desa Kopeng, Kecamatan Getasan, Kabupaten Semarang) - Bayu Setyoko; Purbayu Budi Santosa (Diponegoro Journal of Economics, 2014)
ABSTRACT Agricultural land conversion is one of the phenomenon in the course of agricultural issues. Therefore, the purpose of the research are to determine the factors that influence farmers decision in converting their agricultural land into non-agricultural land. The impacts toward farmers welfare and the impact on socio-environental life in Kopeng.The research applies quantitative approach and uses multiple regression analysis in analyzing factors that influence farmers’ decision in converting their agricultural land into non-agricultural land. Furthermore, the write applies descriptive qualitative approach in analyzing agricultural land conversion impact on farmers’ welfare and socio-environmental condition resulted from the land conversion in Kopeng.As the result of the research, there are four factors which are influencing farmer’s decision in land conversion, they are: 1) economical factor, 2) scial factor, 3) lanf condition factor and 4) government regulations. The land conversion impacts toward the welfare of farmers around the converted land are agrarian structure change, employment change, work pattern change, and income structure change. The field research also proves that the land conversion process change social pattern of the local society. The social impact af the land conversion are viewed fom relationship and interaction between individuals, security, and lifestyle of the society around. Moreover, the land conversion also creates environmental impacts, in regards with household need of water, environmental degradation in the loss of green lands and the fading of natural resource and wisdom that Kopeng has.